2021
DOI: 10.3390/biom11111550
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Immunothrombosis by SARS-CoV-2

Abstract: SARS-CoV-2 contains certain molecules that are related to the presence of immunothrombosis. Here, we review the pathogen and damage-associated molecular patterns. We also study the imbalance of different molecules participating in immunothrombosis, such as tissue factor, factors of the contact system, histones, and the role of cells, such as endothelial cells, platelets, and neutrophil extracellular traps. Regarding the pathogenetic mechanism, we discuss clinical trials, case-control studies, comparative and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 137 publications
1
10
0
Order By: Relevance
“…[7]. One explanation for vascular thrombi in the background of COVID-19 could be related to the angiotensin-converting enzyme 2 (ACE2) receptor and cytokine storms [8,9]. The binding and activation of the ACE2 receptor will cause damage to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7]. One explanation for vascular thrombi in the background of COVID-19 could be related to the angiotensin-converting enzyme 2 (ACE2) receptor and cytokine storms [8,9]. The binding and activation of the ACE2 receptor will cause damage to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Falasca et al reported a series of 22 autopsies on decedents with severe COVID-19 infection and demonstrated prominent microvascular damage and thrombosis [ 7 ]. One explanation for vascular thrombi in the background of COVID-19 could be related to the angiotensin-converting enzyme 2 (ACE2) receptor and cytokine storms [ 8 , 9 ]. The binding and activation of the ACE2 receptor will cause damage to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NETs, damage-associated molecular patterns, oxygen radicals, and many other factors are involved in this pathway. 17 In the SARS-CoV-2 specific pathway, the reaction is initiated by the binding of virus spike protein to its receptor. SARS-CoV-2 infects host cells by binding spike protein to angiotensin-converting enzyme 2 (ACE2), expressed on alveolar epithelial cells, enterocytes, monocytes/macrophages, platelets, and vascular endothelial cells.…”
Section: Platelet Activation In Covid-19mentioning
confidence: 99%
“…Platelets also express proteins, which if localized in the extracellular milieu and possibly conveyed by pEVs, may stimulate inflammation due to molecular profiles. These molecules, known as damage-associated molecular patterns (DAMPs), include highmobility group box 1 (HMGB1) and calprotectin (S100A8/9), which have been identified in numerous inflammatory conditions such as systemic sclerosis, systemic lupus erythematosus, and COVID-19 [122][123][124][125][126][127].…”
mentioning
confidence: 99%